If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -3(4x) = 5(2 + -1x) + 4x Remove parenthesis around (4x) 2 + -3 * 4x = 5(2 + -1x) + 4x Multiply -3 * 4 2 + -12x = 5(2 + -1x) + 4x 2 + -12x = (2 * 5 + -1x * 5) + 4x 2 + -12x = (10 + -5x) + 4x Combine like terms: -5x + 4x = -1x 2 + -12x = 10 + -1x Solving 2 + -12x = 10 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 2 + -12x + x = 10 + -1x + x Combine like terms: -12x + x = -11x 2 + -11x = 10 + -1x + x Combine like terms: -1x + x = 0 2 + -11x = 10 + 0 2 + -11x = 10 Add '-2' to each side of the equation. 2 + -2 + -11x = 10 + -2 Combine like terms: 2 + -2 = 0 0 + -11x = 10 + -2 -11x = 10 + -2 Combine like terms: 10 + -2 = 8 -11x = 8 Divide each side by '-11'. x = -0.7272727273 Simplifying x = -0.7272727273
| -4x-35=3x | | 4k-(2k-5)=0 | | 8y=15y-13 | | 5(x-2)+x=6(8+3)-4x | | C+(c+2)+(c+4)=-57 | | 1+2log(x+1)=log(2x+1)+log(5x+8) | | 3x-5-4x=10+65-3x | | 1+2lg(x+1)=lg(2x+1)+lg(5x+8) | | y^2-11y+36=0 | | 2x+1+2(2-x)=x | | 12=5x+3y | | 5-3(a-12)+a= | | 128=6x*8 | | F(6)=3x-14 | | 28+12x=8x+4 | | 8m-3=13+3+8m+7 | | 2x+40=7x | | 2x-5=1+2x-6 | | 3x+2(x+6)=9x+4 | | x^2+3x=128 | | 5t-3t+18t-2+t=12 | | -x+14y=-19 | | 5-7=6 | | 17=221/x | | -8/3*(-7/9) | | X^2+3x-10=3 | | -4(8+6x)=32+8x | | 4t+9=-7m+18 | | 2/8=7 | | f(3x)=3x^3-18x^2+3 | | 3/8x-6 | | 2x+26y=14 |